Food aid for internally displaced persons in Manicaland, Zimbabwe - Sithole, Wonesai; Coetzee, Jan K (Africanus: Journal of Development Studies, 2018)
<span style="color: #000000; font-family: 'Arial Narrow', Arial, Helvetica, Tahoma, Geneva, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Internally displaced persons (IDPs) are among the most neglected and vulnerable populations in the world. There are few laws that protect them as the government is the instigator of the displacement and no government can be both perpetrator and protector. Food aid has become one of the major protective interventions aimed to enhance stability in settings of displacement. However, a major question is how food aid affects IDPs. The study on which this article is based, was designed to investigate and evaluate how food aid affects the lives of displaced persons. The focus is on understanding the effects of food aid on households' food security, migration trends and asset loss during periods of displacement. The study employs the sustainable livelihood framework in analyzing the role of food aid on IDPs. It focuses on the relationship between food aid and livelihoods assets, and indicates how the transforming structures can be linked to food aid interventions. The findings show that food aid plays a significant role in cushioning displaced households provided that it is integrated with other sustainable livelihood interventions (such as those that promote the value of household assets and land holding). Due to denied access to land, IDPs are dependent on food aid for their household food security. Increased school attendance is noted because of food aid to IDPs but the absence of security of tenure hinders community driven effective alternatives to a food aid programme. If security of tenure is not addressed IDPs in Manicaland will find it difficult to deal with their food insecurity.